PENGOLAHAN PAKAN SAPI DAN PUPUK BOKASHI PADA PETERNAK SAPI DI DESA ALEBO KECAMATAN KONDA - Hafid, Harapin; Tasse, Andi Murlina; Pancar, Fadli Ma’mun; Surahmanto, La Ode (Anoa : Jurnal Pengabdian Masyarakat Sosial, Politik, Budaya, Hukum, Ekonomi, 2023)
People in Alebo village, Konda subdistrict, South Konawe Regency, are very familiar with cattle farming because almost all of them raise cattle and work as vegetable and secondary crop farmers. The aim of this activity is to teach how to prepare feed formulations and process drum manure into bokashi fertilizer so that the livestock community gets added value in the form of side income. In the process of raising cattle, these breeders do not optimally understand the system of raising cattle properly and correctly, especially the issue of feed formulation and processing manure into organic fertilizer. This is due to the limited knowledge and skills of farmers in managing their cattle farming business, especially providing feed and managing livestock waste. Based on the results of discussions with farmers, the target to be achieved after implementing the village development program is to increase the knowledge and skills of farmers regarding ration formulation techniques as cattle feed that meet quality standards by utilizing local feed raw materials, and processing livestock waste into fertilizer bokashi.